Psychosocial factors associated with occupation: A comparative study between brick kiln and grocery workers - Sanjel, Seshananda; Khanal, Sanjay N.; Risal, Ajay; Thygerson, Steven M.; Joshi, Sunil K. (International Journal of Occupational Safety and Health, 2016)
Background: Psychosocial factors, like physical, chemical and biological factors, are also the potential hazards. But, psychological factors, such as stress, are not mentioned in every kinds of occupation. Some important psychosocial manifestations found among the workers in previous studies were headache, depression, frustration, worry, low self-esteem, boredom and lack of sleep. Objective: This study was carried out to evaluate and psychosocial factors that are associated with occupational factor between brick kiln workers and grocery workers. Methods: An analytical cross-sectional study was conducted in Kathmandu Valley during February-March 2015 i, targeting all the brick kiln workers. Firstly, all the registered the brick kilns (106 in number) were visited to form the potential sampling frame. Multi-stage probability proportionate to size sampling was applied to select 400 brick kiln workers from 16 brick kilns who had been working there for more than two years. An equal size unmatched reference group was maintained from the grocery workers. Interviews were conducted by trained health workers. Data was entered in the Microsoft (MS) excel and was transferred into the International Business Machines (IBM) Corporation. Statistical Package for the Social Sciences (SPSS) Statistics 21 was used to perform analysis. Both descriptive and (mean, median and inter-quartile range) and inferential (Mann Whitney U test) statistics were computed. The level of significance was set at <0.05. Results: Nearly 20.0% of exposed workers were <19 years of age among which slightly above three fifth achieved primary education. Almost 40% of brick kiln workers were ever smokers. Positive factors of psychosocial and emotional functioning were lower and negative factors were higher among brick kiln workers. The parameters of relationships such as self-esteem, stress and personal agency and the parameters of emotions like emotional, somatic, chronic fear, anxiety, hopelessness, helplessness, abuse and mal-treatment were better and significantly better respectively, in the reference group than the exposed group. However, the social factor was significantly poor among the reference group i.e. the grocery workers as observed while conducting Mann Whitney U test at p<0.05 level. Conclusion: Among most of the parameters, brick kiln workers' psychosocial functioning was significantly poorer than the grocery workers. Providing formal and/or non-formal education as well as raising awareness about the deleterious effects of the exposure to brick kiln workers should be recommended.